Efektifitas Pemanfaatan Repository Perguruan Tinggi: Studi pada Perpustakaan IPDN Kampus Jatinangor - Rahmadanita, Annisa; Hidayat, Enjang (Perpustakaan Universitas Gadjah Mada, 2023)
IPDN library has been providing college repository services since 2017 through eprints.ipdn.ac.id, but there has been no measurement related to the effectiveness of the utilization of the IPDN repository service. The purpose of this study is to obtain a general overview of the effectiveness of the use of University repositories in the IPDN Library Jatinangor campus. The study used qualitative methods with data collection through interviews to 15 informants, observation and documentation. The results showed that the IPDN Repositori is provided with the aim to provide convenience for users, especially IPDN lecturers in the storage and assessment of scientific work, but there are still server and network constraints at the time of its utilization. In addition, the IPDN Library has conducted socialization and assistance for users. However, monitoring activities related to the utilization of IPDN repository services are still minimal. In conclusion, the effective utilization of University repositories, especially in the Institute of domestic government (IPDN) is included in the sufficient category. As for the 4 (four) dimensions that become a measure of effectiveness, there is 1 (one) dimension that is still lacking in its application, namely the monitoring dimension, 2 (two) dimensions that are sufficient, namely the dimension of targeting and program goals, 1 (one) dimension that is good, namely the dimension of socialization.